Конституційно-правовий статус дітей з обмеженими можливостями : автореф. дис. - Філіпська, Н. О.; Filipska, N. O.; Филипская, Н. А. (Харків, 2016)
Дисертація присвячена дослідженню конституційно-правового статусу дітей з обмеженими можливостями. Досліджено генезу прав та свобод даної категорії осіб. Проаналізовано структуру конституційно-правового статусу, його основні елементи, визначено специфіку його елементного складу. У рамках конституційно-правового статусу «дитина з обмеженими можливостями» виокремлено 6 субстатусів у залежності від характеру обмеження життєдіяльності. Досліджено міжнародно-правові стандарти забезпечення прав дітей з обмеженими можливостями та стан їх реалізації в Україні. На підставі аналізу світового досвіду з'ясовано можливості його запозичення та адаптації. Впорядковано та проаналізовано нормативно-правову базу, що регулює конституційно-правовий статус, систематизовано права і свободи зазначеної категорії осіб. Досліджено стан та проблеми реалізації цих прав, запропоновано шляхи розв’язання виявлених проблем. Як результат аналізу системи гарантій прав цих дітей сформовано пропозиції щодо внесення змін у чинне законодавство України.

The thesis is devoted to the research of constitutional and legal status of children with disabilities. The structure of constitutional and legal status has been analyzed; its elemental composition has been elucidated. The features of such elements as legal norms, legal personality, legal responsibility have been found out. The author grounds the necessity of separating the category “children with disabilities” into 6 sub-categories (where each has the relevant sub-status): 1) children who actually have some (minor) health problems (physical, psychological and intellectual or complex), but having no status of “disabled child” for various reasons; 2) children with impaired physical health not related to psychological and intellectual, sensory disorders and disorders of the musculoskeletal functions of the body; 3) children whose conditions do not limit the psychological and intellectual development of a child, but affect the musculoskeletal functions of the body; 4) children with impaired sensory functions of the body; 5) children with disorders of psychological and intellectual nature without limitation of motor functions of the body; 6) children with disabilities of integrated nature, i.e. limitation of both psychological and intellectual, and physical health. Research of the genesis of the rights and freedoms of this category of persons allowed to single out five major historical periods of the formation and development of the rights of children with disabilities: from the emergence of humanity and to the Middle Ages – the period of opposition to the rights of children in general and those with malformations and disorders of health in particular; from the IX-X centuries – to the end of the XVIIIh century – “religious and charity” period; the end of XVIII – XIX centuries – “medical and social” period; the end of XIX – XX centuries – the period of “strengthening capacity”; XXI century – the period of “equal opportunities”. International and legal standards for guaranteeing the rights of children with disabilities and the state of their implementation in Ukraine have been studied. Based on the analysis of the world experience the author has revealed the possibility of its borrowing and adaptation. The normative and legal base regulating the constitutional and legal status has been gradated and analyzed; the rights and freedoms of this category of people have been systematized and divided into 7 sub-groups (the right to an adequate standard of living and social protection; the rights to housing that meets the requirements and needs and to unimpeded environment; the rights to education and vocational training; the rights to personal development and the cultural development; the rights to work; the rights of parents (or persons substituting them) who up-bring children with disabilities). The existing forms and methods of realizing the rights and freedoms of this category of persons and guaranteeing unimpeded environment have been researched. The author has suggested a number of innovative forms (providing access to information, “early intervention”), methods (adaptation of art works, “light language”) and guarantees of implementation (creation of a single codified act regulating the legal status of persons with disabilities, individualization of the items of the state and local budgets in this area, etc.) of the rights of this category of persons (taking into account their specific features). As a result of the analysis of the system of guarantees of these children’s rights the author has formed propositions for amending the current legislation of Ukraine.

Диссертация посвящена исследованию конституционно-правового статуса детей с ограниченными возможностями. Проведено исследование происхождения прав и свобод данной категории лиц. Проанализирована структура конституционно-правового статуса, его основные элементы, определена специфика его элементного состава. В рамках конституционно-правового статуса «ребенок с ограниченными возможностями» выделено 6 субстатусов в зависимости от характера ограничения жизнедеятельности. Исследованы международно-правовые стандарты обеспечения прав детей с ограниченными возможностями и состояние их реализации в Украине. На основании изучения мирового опыта определены возможности его заимствования и адаптации. Упорядочена и проанализирована нормативно-правовая база, регулирующая конституционно-правовой статус, систематизированы права и свободы данной категории лиц. Изучено состояние и проблемы реализации этих прав, предложены пути решения выявленных проблем. Как результат анализа системы гарантий прав этих детей сформированы предложения о внесении изменений в действующее законодательство Украины.
Автореферат дисертації на здобуття наукового ступеня кандидата юридичних наук
Конституционно-правовой статус детей с ограниченными возможностями
Філіпська, Н. О. Конституційно-правовий статус дітей з обмеженими можливостями : автореф. дис. ... канд. юрид. наук : 12.00.02 / Н. О. Філіпська; МВС України, Харк. нац. ун-т внутр. справ. - Харків, 2016. - 20 с.
Keywords: Конституційне право. Constitutional Law. Конституционное право; Автореферати дисертацій. Abstracts of Theses. Авторефераты диссертаций; 12.00.02; Україна. Ukraine. Украина; діти з обмеженими можливостями; субстатус; інклюзія; індивідуальна програма реабілітації; безбар'єрне середовище; адвокасі; інформаційна доступність; конституційно-правовий статус; дети с ограниченными возможностями; инклюзия; индивидуальная программа реабилитации; безбарьерная среда; адвокаси; информационная доступность; children with disability; substatus; inclusion; individual program of rehabilitation; surroundings without barriers; advocacy; information accessibility; конституционно-правовой статус; constitutional and legal status